Navigating the complex pathway of youth athletic development: Challenges and solutions to managing the training load of youth team sport athletes - Scantlebury, S.; Till, K.; Sawczuk, T.; Phibbs, P.; Jones, B. (Strength and Conditioning Journal, 2020)
The development of a youth team sport athlete is a complex process. This article outlines challenges that may restrict the optimal balance between training and recovery and provide solutions to help practitioners overcome these challenges. To facilitate positive youth athletic development, training aims must be aligned between stakeholders to synchronize periods of intensified training and recovery. Within- and between-athlete variations in weekly training load must be managed and practitioners should attempt to ensure the intended load of training equals the load perceived by the athlete. Furthermore, practitioners should be cognizant of the athletes' nonsport-related stressors to enable both academic and sporting pursuits. Although each of these challenges adds intricacy, they may be overcome through collaboration, monitoring, and, if necessary, the modification of the athletes' training load.